The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-64284-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of season on the association between vitamin D levels at diagnosis and one-year remission in early Rheumatoid Arthritis

Abstract: the study evaluates associations between serum vitamin D metabolites at diagnosis and one-year remission, in early diagnosed rheumatoid arthritis(RA). The CIMESTRA-cohort comprised 160 newly diagnosed RA patients, treated aiming at remission. Vitamin D supplementation was recommended according to national guidelines. D total (25OHD 2 + 25OHD 3) was dichotomized at 50 nmol/L, 1,25(OH) 2 D was categorized in tertiles. Primary outcome was remission(DAS28-CRP ≤ 2.6) after one year. Associations were evaluated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In addition, the season of clinical onset of RA, according to data from 736 patients with RA in a multicentre study, seems to predict the severity of the disease. In fact, RA onset during spring or winter (with low exposure to solar UVB and hence low synthesis of vitamin D) rather than summer or autumn was reportedly associated with faster erosive radiographic progression (already at 6 months), together with a lower probability of disease remission at 1 year 189 , 190 .…”
Section: Vitamin D and Seasonal Rhythms Of Autoimmune Rheumatic Diseasesmentioning
confidence: 99%
“…In addition, the season of clinical onset of RA, according to data from 736 patients with RA in a multicentre study, seems to predict the severity of the disease. In fact, RA onset during spring or winter (with low exposure to solar UVB and hence low synthesis of vitamin D) rather than summer or autumn was reportedly associated with faster erosive radiographic progression (already at 6 months), together with a lower probability of disease remission at 1 year 189 , 190 .…”
Section: Vitamin D and Seasonal Rhythms Of Autoimmune Rheumatic Diseasesmentioning
confidence: 99%
“…Seasonal variations in 25-OH-D concentration depend on geographic location and is a factor that can lead to seasonal differences in RA activity [13,[36][37][38]. A study on the Swedish population revealed a significant seasonal variation in 25-OH-D concentration associated with the intensity of UV-B irradiation [36].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the weekly high dose of cholecalciferol compared to monthly therapy with the same dose was not only safe, effective, and faster in increasing 25(OH)D serum levels, but also associated with a greater improvement of muscular function (Corrado, Rotondo, Cici, Berardi, & Cantatore, 2021). Additionally, low vitamin D is associated with a low rate of one-year remission in patients with early rheumatoid arthritis whose diagnosis was established in winter (Herly et al, 2020). Also, it has been shown that in RA patients a better response to Tocilizumab (anti-IL-6 antibodies) when patients have sufficient serum vitamin D. Tocilizumab and 1,25(OH)2D synergistically suppress IL-17 production and osteoclast differentiation (Kim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%